(untitled) (AGROINNOVATSIYА, 2024)
This article provides information on the origin, distribution, biological properties, chemical composition, valuable economic signs and medicinal properties of monarda (Monarda L) plant. In addition, recommendations were given on the importance of choosing and growing varieties suitable for the climate of the Surkhandarya region.